2019
DOI: 10.1111/anu.12883
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary glutamine supplementation on growth performance, antioxidant status and intestinal function in juvenile grass carp (Ctenopharyngodon idella)

Abstract: Glutamine (Gln) is a conditionally essential free amino acid that has been widely used in aquaculture. The present study showed that appropriate levels of dietary Gln could significantly improve growth performance and increase lipase and trypsin activity, mucosal thickness (MT) and the number of lymphocytes. The levels of glycine (Gly) in the 6 g/kg Gln group, threonine (Thr) in the 12 g/kg group and lysine (Lys) in the 6 and 9 g/kg group were increased significantly, while glutamate (Glu) and serine (Ser) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 57 publications
3
4
0
Order By: Relevance
“…In this study, we found that the additions of glutamate and glutamine in daily feed increased the FCR and FR in triploid crucian carp. These results were consistent with the research in Atlantic salmon (Salmo salar L.) and grass carp [37,38]. By comparing the effects of glutamate additive on expression levels of ASCT2 between intestine and muscle, we found they had a similar trend.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we found that the additions of glutamate and glutamine in daily feed increased the FCR and FR in triploid crucian carp. These results were consistent with the research in Atlantic salmon (Salmo salar L.) and grass carp [37,38]. By comparing the effects of glutamate additive on expression levels of ASCT2 between intestine and muscle, we found they had a similar trend.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, X. davidi fed with 6 g/kg and 9 g/kg of glutamine showed signi cant improvements in growth performance, which indicate that the appropriate levels of glutamine can promote sh growth. Similar ndings have been reported on half-smooth tongue sole (Cynoglossus semilaevis Günther) (Jingwei, et al, 2015), grass carp (Ctenopharyngodon idella) (Qu, et al, 2019), Jian carp (Cyprinus carpio var. Jian) (Hu, et al, 2015).…”
Section: Discussionsupporting
confidence: 83%
“…Glutamine increased the e ciency of the sh to utilise nutrients on their own, which was a key factor for the improved growth performance. Moreover, glutamine can improve sh intestine function with the improvement of intestinal structure and enhances the release of digestive enzymes (Chen, et al, 2009;Pohlenz, et al, 2012;Qu, et al, 2019), such like the way 6 g/kg and 9 g/kg group did. However, the growth performance of sea cucumber (Apostichopus japonicus Selenka) (Yu, et al, 2016) and Nile tilapia (Oreochromis niloticus) (Pereira, et al, 2017) was found to be reduced after feeding diets supplemented with high level of glutamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results agree with previous studies showing immunostimulant mixtures can beneficially affect digestive enzymes in fish 71 . Specifically, glutamine has been shown to stimulate production of digestive enzymes and regulate absorption of amino acids 72 . Similar effects of yeast supplements on enzyme activity were seen in shrimp fed fermented soybean meal 73 .…”
Section: Discussionmentioning
confidence: 99%